Practising Corporate Social Responsibility in Malaysia A Case Study in an Emerging Economy - Teck Hui, Loi (Springer International Publishing, 2018)
This book takes a unique approach exploring Corporate Social Responsibility through a case study in Bintulu, Malaysia. Drawing upon major CSR and strategy theories, the author examines how CSR is embedded in the organizational strategic planning processes of two prevalent forms of governmental institutions, a development agency and a city council. Exploring the impact of triple bottom line in easing tensions between shareholders and stakeholders, this book provides a qualitative narrative on a holistic CSR process in order to assess the contribution and value of CSR to a firm's sustained value created capability.